Towards A Sustainable Islamic Banking System: Re-embedding Murabaha Mode of Financing - Jatmiko, Wahyu (UI Scholars Hub, 2017)
This study is an attempt at solving the chronic problems of banking murabaha, notably the ribawi benchmark rate problem. To this end, the first stage of this study examines whether the recent solution for banking murabaha, namely Islamic Interbank Benchmark Rate (IIBR), is a sustainable solution to solve the problem. The Johansen cointegration test between IIBR and LIBOR, as an international benchmark rate, as well as IIBR and JIBOR, as an Indonesian one, is performed to prove that notion. The results suggest that IIBR has long-run equilibrium relationship with the two ribawi benchmark rates. IIBR hence does not fulfil the sustainability feature as a long-run solution for Islamic finance. The second stage of this study proposes the so-called universal Islamic banking system as a solution to remedy the problem. The proposed model is not only theoretically appealing but also practically possible to be implemented.